CLINICAL PHARMACOLOGICAL APPROACH TO THE RATIONAL USE OF VITAMINS IN CHILDREN - Parpiyeva Salima Boqijonovna (Galaxy International Interdisciplinary Research Journal, 2024)
Modern data on the participation of vitamin D in the formation of various forms of allergic pathology in children are presented. The range of knowledge about the biological significance of vitamin D has recently expanded significantly. The features of vitamin D metabolism and its participation in the leading links in the pathogenesis of atopic dermatitis (AD) are described: in the regulation of the immune response, violations of the integrity of the epidermal barrier and the implementation of allergic inflammation in the skin. The pathogenetic significance of vitamin D deficiency in the formation of bronchial asthma (BA) is discussed.